2015
DOI: 10.1038/pr.2015.269
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes induces alterations of sirtuins in fetal endothelial cells

Abstract: Background: Gestational diabetes (GDM) has long-term consequences for the offspring. Sirtuins (SIRTs) are associated with vascular and metabolic functions. We studied the impact of GDM on SIRT activity and expression in fetal endothelial colony-forming cells (ECFCs) and human umbilical vein endothelial cells (HUVECs) from pregnancies complicated by GDM. Methods: ECFCs and HUVECs were isolated from cord and cord blood of 10 uncomplicated pregnancies (NPs) and 10 GDM pregnancies. Nicotinamidadenindinukleotid (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…It was demonstrated that SIRT1 overexpression can improve glucose metabolism and insulin signaling [60]. On the other hand, oxidative stress and hyperglycemia can decrease SIRT1 protein and gene expression in diabetic patients [12,61]. Nevertheless, our data showed no alteration in SIRT1 expression in placental or umbilical-cord blood cells.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…It was demonstrated that SIRT1 overexpression can improve glucose metabolism and insulin signaling [60]. On the other hand, oxidative stress and hyperglycemia can decrease SIRT1 protein and gene expression in diabetic patients [12,61]. Nevertheless, our data showed no alteration in SIRT1 expression in placental or umbilical-cord blood cells.…”
Section: Discussionmentioning
confidence: 48%
“…SIRT1 is an important determinant of human longevity and a positive regulator of telomere length through modulation of telomerase activity and homologous recombination repair [11]. Decreased expression was detected in fetal endothelial colony-forming cells from pregnancies complicated by GDM, and provided potential mechanistic insights into the pathophysiology of long-term cardiovascular complications observed in the offspring of GDM pregnancies [12]. Indeed, some studies have associated (sub)telomere maintenance and also mitochondrial biogenesis with SIRT1 and TP53 [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For SIRT1, modulation of expression was described via carboxyl terminus binding protein (CtBP) [52]. Furthermore, SIRT1 gene expression was regulated in hypoxia in a HIF-dependent manner [76]. The CREB (cAMP-responsive element protein-binding) protein was able to regulate SIRT1 expression in response to the NAD/NADH-levels [77].…”
Section: Discussionmentioning
confidence: 99%
“…These studies were carried out to provide some insight into the dysfunction associated with ECFCs exposed to a diabetic environment. The research on UC-ECFCs from G-DM pregnancies has shown that the diabetic intrauterine environment also reduces the number of UC-ECFC colonies and their functionality in the form of reduced tubulogenic capacity, reduced proliferation, reduced migration and that G-DM UC-ECFCs have reduced sirtuin1 and sirtuin3, which are involved with regulating cell metabolism and aging, compared to UC-ECFCs from healthy pregnancies [33,34]. Dincer [35] demonstrated that G-DM UC-ECFCs were less tolerant to hypoxic environments, resulting in increased senescence and decreased tubulogenesis in hypoxic conditions compared to ECFCs from healthy controls.…”
Section: Uc-ecfcs From Gestational Diabetes Pregnanciesmentioning
confidence: 99%